The Effect of Customer Satisfaction on Trust and Repurchase Interest in Cushion Somethinc Products at Panda Lovely Pasuruan Branch - Lailatul Fitriya; Nur Azizah (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
In modern times, many people are starting to know cosmetics and are more concerned with appearance, not only from the fashion worn but also from the makeup and skincare used on the face. Somethic is one of the local brands that has many variants for treatments and makeup. This study aims to determine the influence between the variables studied. These variables include customer satisfaction, trust and repurchase interest. This type of research is quantitative research with an explanatory approach where it is used to test the relationship between variables or find out whether a variable is caused or manipulated by other variables or not. The data collection technique used was a questionnaire that was distributed offline to somethic product users who made purchases at branches on lovely Pasaruan. The sample used in this study is 100 respondents using the purposive sampling method where the selected sample is required to be in accordance with the criteria needed with the suitability of the research objectives. In data management, this research was carried out using the Partial Least Square (PLS) analysis method. Based on the results of this study, it can be seen that customer satisfaction has a positive and significant effect on repurchase interest and trust has a positive and significant effect on repurchase interest.